Atomic Layer Deposition of Bismuth Vanadates for Solar Energy Materials. Issue 13 (1st June 2016) - Stefik, Morgan
Abstract: The fabrication of porous nanocomposites is key to the advancement of energy conversion and storage devices that interface with electrolytes. Bismuth vanadate, BiVO4, is a promising oxide for solar water splitting where the controlled fabrication of BiVO4 layers within porous, conducting scaffolds has remained a challenge. Here, the atomic layer deposition of bismuth vanadates is reported from BiPh3, vanadium(V) oxytriisopropoxide, and water. The resulting films have tunable stoichiometry and may be crystallized to form the photoactive scheelite structure of BiVO4 . A selective etching process was used with vanadium‐rich depositions to enable the synthesis of phase‐pure BiVO4 after spinodal decomposition. BiVO4 thin films were measured for photoelectrochemical performance under AM 1.5 illumination. The average photocurrents were 1.17 mA cm −2 at 1.23 V versus the reversible hydrogen electrode using a hole‐scavenging sulfite electrolyte. The capability to deposit conformal bismuth vanadates will enable a new generation of nanocomposite architectures for solar water splitting. Abstract : Solar Energy Materials : Bismuth vanadates of tunable composition are fabricated using atomic layer deposition (ALD). ALD allows the first production of bismuth vanadates deposited in a conformal fashion onto arbitrary substrates. The films are calcined to yield the photoactive scheelite phase and are capable of efficient solar‐assisted water splitting with thin‐film photocurrents greater than 1 mA cm −2 under simulated AM 1.5 illumination.